Multi-Branch Tomlinson-Harashima Precoding for Rate Splitting Based Systems with Multiple Antennas - Flores, A. R.; de Lamare, R. C.; Clerckx, B. (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2021)
Rate splitting (RS) has emerged as a valuable technology for wireless communications systems due to its capability to deal with uncertainties in the channel state information at the transmitter (CSIT). RS with linear and non-linear precoders, such as the Tomlinson- Harashima (THP) precoder, have been explored in the downlink (DL) of multiuser multi antenna systems. In this work, we propose a multi-branch (MB) scheme for a RS-based multiple-antenna system, which creates patterns to order the transmitted symbols and enhances the overall sum rate performance compared to existing approaches. Analytical expressions to describe the signal-to-interference-plus- noise ratio (SINR) and compute the sum rate are derived. Simulation results show that the proposed MB-THP for RS outperforms conventional THP and MB-THP schemes.